Viseral Organ Belibis Kembang Yang diberi Pakan Dengan Level Protein Berbeda: Visceral Organ Weight Of Wandering Whistling Ducks Fed Different Protein Levels - Jamilah; Mahfudz, Luthfi Djauhari; Suprijatna, Edjeng; Wahyuni, Hanny Indrat (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to determine the effect of different protein levels on the visceral organ of wandering whistling ducks. 108 ducks were reared for three months with details of 1 month of feed adaptation period and 2 months of feed treatment with different protein levels. This study consisted of 3 treatments, namely P1 with 12% protein , P2 with 15% protein , and P3 with 18% protein. Each treatment consisted of 9 replications, and each experimental unit consisted of 4 5-month-old wandering whistling ducks. The parameters measured in this study were the weight of the visceral organs of wandering whistling ducks (liver, heart, pancreas, and lungs). The data obtained were analyzed for variance, if there were significant differences a further test was carried out with Duncan's test. The results of this study indicated that the protein level had no significant effect (P>0.05) on the visceral organs of wandering whistling ducks. The lowest protein level, namely 12%, did not have a negative effect on the visceral organs of wandering whistling ducks.This study can be concluded that the protein level of 12% -18% in a feed of wandering whistling ducks has the same effect on the development of visceral organs.